Spremembe oblike cestišča pri različnih načinih investicijskega vzdrževanja gozdne ceste - Robek, Robert (Zbornik gozdarstva in lesarstva, 1999)
Optimisation of the forest road network maintenance calls for a network of themodel road sections where the inputs and long term effects of implemented measures can be monitored and evaluated. On four model sections of the forest road we investigated the short-term alterations of the roadway shape after periodic maintenance with minimal and optimal addition of autochthon gravel and the two methods of pavement: two passes of a roller and paving with truck traffic. On the basis of the numerical analysis of roadway cross-section data significant decrease of the transverse roughness index (TRI) for thin gravelled profiles and insignificant increase of TRI on unrolled profiles after road use were found. The average carriageway transverse gradient, the average roadway width and the average ditch depth have not significantly changed after applied maintenance modes. The width of longitudinal road drainage installations was in most cases altered at the expense of carriagewaywidth, its depth increased in all applied modes. Long term effects of the implemented modes should be monitored and verified on similar model sections in various geological and climatic conditions, which requires seriousconsideration of the forest road model section network concept. Key words: forest road, roadway maintenance, rolling, transverse roughness index, model sections
Keywords: cestišča; gozdne ceste; vzdrževanje cest